2023
DOI: 10.1038/s42003-022-04398-2
|View full text |Cite
|
Sign up to set email alerts
|

Aβ efflux impairment and inflammation linked to cerebrovascular accumulation of amyloid-forming amylin secreted from pancreas

Abstract: Impairment of vascular pathways of cerebral β-amyloid (Aβ) elimination contributes to Alzheimer disease (AD). Vascular damage is commonly associated with diabetes. Here we show in human tissues and AD-model rats that bloodborne islet amyloid polypeptide (amylin) secreted from the pancreas perturbs cerebral Aβ clearance. Blood amylin concentrations are higher in AD than in cognitively unaffected persons. Amyloid-forming amylin accumulates in circulating monocytes and co-deposits with Aβ within the brain microva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
(145 reference statements)
1
12
0
Order By: Relevance
“…Amylin is a 37 amino acid long pancreatic hormone and co-secreted with insulin from beta cells ( 15 18 ). Studies from our lab and from other labs showed amylin have novel function in renal function and path-physiology and also in other organs ( 19 24 ). A recent study from our lab showed that red blood cell (RBC)-capillary interaction is altered by prediabetic hypersecretion of amylin that could be a potential contributing factor to renal hypoxia in diabetic kidney injury ( 19 ).…”
Section: Introductionmentioning
confidence: 56%
“…Amylin is a 37 amino acid long pancreatic hormone and co-secreted with insulin from beta cells ( 15 18 ). Studies from our lab and from other labs showed amylin have novel function in renal function and path-physiology and also in other organs ( 19 24 ). A recent study from our lab showed that red blood cell (RBC)-capillary interaction is altered by prediabetic hypersecretion of amylin that could be a potential contributing factor to renal hypoxia in diabetic kidney injury ( 19 ).…”
Section: Introductionmentioning
confidence: 56%
“…Hence, these chemicals and other waste products need to be treated and eliminated or converted to other non-hazardous products; in order to achieve this, they need to be identified and quantified [ 12 , 13 , 14 ]. Therefore, it is indispensable to detect and quantify various significant analytes, from biofluids to environmental samples, in order to prevent or eliminate various diseases and disorders [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistological stainings show that IAPP often co-localizes with Aβ42 in plaques and Aβ40 in vessel walls [ 14 , 15 ]. Furthermore, a recent study using human and animal models has demonstrated that pancreas-derived IAPP accumulates in circulating monocytes and co-deposits with Aβ within the brain microvasculature, further inducing cerebrovascular inflammation [ 18 ]. IAPP (and its non-amyloidogenic analogue pramlintide) also plays a crucial role in Aβ brain-to-blood clearance [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study using human and animal models has demonstrated that pancreas-derived IAPP accumulates in circulating monocytes and co-deposits with Aβ within the brain microvasculature, further inducing cerebrovascular inflammation [ 18 ]. IAPP (and its non-amyloidogenic analogue pramlintide) also plays a crucial role in Aβ brain-to-blood clearance [ 18 , 19 , 20 ]. Interestingly, this clearance, especially of Aβ40, is attenuated in the presence of APOE4 [ 21 ], leading to an exacerbated IAPP deposition and vascular pathology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%